2020
DOI: 10.2196/12306
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Health Benefits of an Individualized Physical Activity Intervention in Women With Metastatic Breast Cancer: Intervention Study

Abstract: Background There is limited knowledge regarding the potential benefits of physical activity in patients with metastatic breast cancer. Objective The Advanced stage Breast cancer and Lifestyle Exercise (ABLE) Trial aimed to assess the feasibility of a physical activity intervention in women with metastatic breast cancer and to explore the effects of physical activity on functional, psychological, and clinical parameters. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 45 publications
2
58
1
Order By: Relevance
“…In the ABLE Trial, we previously found that the intervention improved functional capacities (i.e., statistically significant and clinically relevant improvements of 6MWD + 7% [69][70][71], isometric quadriceps strength + 22%) and that muscular strength was maintained despite the progress of the disease and treatment [55]. To our knowledge, only one randomized controlled trial conducted among 200 patients with localized breast cancer receiving adjuvant chemotherapy has assessed the impact of resistance and aerobic exercise on sarcopenia [35].…”
Section: Discussionmentioning
confidence: 99%
“…In the ABLE Trial, we previously found that the intervention improved functional capacities (i.e., statistically significant and clinically relevant improvements of 6MWD + 7% [69][70][71], isometric quadriceps strength + 22%) and that muscular strength was maintained despite the progress of the disease and treatment [55]. To our knowledge, only one randomized controlled trial conducted among 200 patients with localized breast cancer receiving adjuvant chemotherapy has assessed the impact of resistance and aerobic exercise on sarcopenia [35].…”
Section: Discussionmentioning
confidence: 99%
“…Early evidence suggests that physical activity interventions are not only safe and low cost, but may improve physical and mental wellbeing among MCS [29][30][31][32][33][34]. Data from CanWalk, a 12-week community-based walking intervention among MCS, show that MCS who walked 30 minutes or more per day reported a higher QOL than those who walked less than 30 minutes per day [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has suggested this population is receptive to technology-based health interventions. In fact, a recent study by Delrieu et al observed BCS to be willing and interested in the use of technology-based interventions to improve HRQoL outcomes, and furthermore, found these interventions to be effective for improving health behaviors such as physical activity participation [ 11 , 12 ]. Further, another study comparing various cancer survivor groups found that BCS, specifically, tended to have the greatest ability to improve physical activity behaviors during a technology-based intervention [ 8 ].…”
Section: Introductionmentioning
confidence: 99%